Application of bacterial ligninase enzymes from rynchophorus ferrugineus’s gut consortium in agropulp biodelignification - Ishak, Nadiah (2018)
Lignin is a complex phenylpropanoid heteropolymer entangled around cellulose and hemicellulose fibre. It is recalcitrant towards degradation, thus pose a major problem in obtaining good quality fibre. Moreover, the conventional degradation methods (chemically and mechanically) consume vast amount of chemicals and energy which have deleterious effects to the environment. The aim of this research is to identify an alternative process for lignin removal by employing ligninase produced by lignin-depolymerising bacteria isolated within the gut of wood feeding insect, Rynchophorus ferrugineus. In this study, four bacterial species capable of depolymerising lignin were isolated, identified and characterised as Klebsiella pneumoniae, Pseudomonas citronellolis, Enterobacter oryzae, and Serratia mercescens. The production of ligninase enzymes (lignin peroxidase, manganese peroxidase and laccase) in all species were optimised using response surface methodology (RSM). The results revealed maximal production of ligninase is achieved at optimal pH of 5 to 6 and optimal temperature of 40 °C after 7 days of incubation. The ability of each specie to remove lignin in agrowastes (cogon grass (CG) and oil palm leaves (OPL)) was validated through UV-Vis spectrophotometer, FTIR and SEM analyses. The results showed that the gut microbes were solely able to degrade lignin with 30 to 60% in OPL and CG respectively, in which the highest delignification is obtained by the combination of all species. Furthermore, traces of small molecular weight compounds generated after the enzymatic breakdowns were identified through HPLC and GC-MS analysis as part of the complementary study. Through the identification of metabolites produced, the conversion pathways of lignin polymer to various aromatic and non-aromatic compounds during the breakdown were also proposed. The findings of this research can be made applicable to the pulp and paper industries thus encouraging the use of green and sustainable technology. The identification of breakdown metabolites could be exploited in the valorization of lignin promoting the concept of „waste to wealth‟.